Reduction in SOCE and associated aggregation in platelets from mice with platelet-specific deletion of Orai1 - Yang, Linlin; Ottenheijm, Roger; Worley, Paul; Freichel, Marc; Camacho Londoño, Juan Eduardo (Cells, 2022)
Calcium signalling in platelets through store operated Ca2+ entry (SOCE) or receptor-operated Ca2+ entry (ROCE) mechanisms is crucial for platelet activation and function. Orai1 proteins have been implicated in platelet’s SOCE. In this study we evaluated the contribution of Orai1 proteins to these processes using washed platelets from adult mice from both genders with platelet-specific deletion of the Orai1 gene (Orai1flox/flox; Pf4-Cre termed as Orai1Plt-KO) since mice with ubiquitous Orai1 deficiency show early lethality. Platelet aggregation as well as Ca2+ entry and release were measured in vitro following stimulation with collagen, collagen related peptide (CRP), thromboxane A2 analogue U46619, thrombin, ADP and the sarco/endoplasmic reticulum Ca2+-ATPase (SERCA) inhibitor thapsigargin, respectively. SOCE and aggregation induced by Thapsigargin up to a concentration of 0.3 µM was abrogated in Orai1-deficient platelets. Receptor-operated Ca2+-entry and/or platelet aggregation induced by CRP, U46619 or thrombin were partially affected by Orai1 deletion depending on the gender. In contrast, ADP-, collagen- and CRP-induced aggregation was comparable in Orai1Plt-KO platelets and control cells over the entire concentration range. Our results reinforce the indispensability of Orai1 proteins for SOCE in murine platelets, contribute to understand its role in agonist-dependent signalling and emphasize the importance to analyse platelets from both genders.